2013
DOI: 10.1155/2013/384527
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Psychotropic Use in Children with High-Functioning ASDs

Abstract: This study examined (1) the prevalence of psychotropic medication use for a sample of children with high-functioning autism spectrum disorders (HFASDs), (2) the extent to which psychotropic agents were linked to targeted symptoms, and (3) predictors of psychotropic use. A total of 115 children, ages 6–13, with HFASDs who were enrolled in psychosocial treatment trials were included in this study. Parents completed extensive background and rating forms prior to treatment that included data on demographic charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
2
1
0
Order By: Relevance
“…The most commonly prescribed medications were antidepressants (32%), followed by stimulants (20%) and neuroleptics (17%). Similar findings are described in a more recent study of psychotropic medication use in children with HFASD where 33% of the sample reported taking psychotropic drugs, with stimulant (25%), antidepressant (10%), and neuroleptic (6%) medications most commonly prescribed [ 60 ]. More general findings for studies of children, adolescents, and adults with ASD suggest that greater age, lower adaptive skills, lower social competence, higher levels of challenging behaviour, and living away from home are all associated with an increased likelihood of medication use [ 54 , 55 , 57 , 58 , 61 , 62 ].…”
Section: Mental Health Interventions In Hfasdsupporting
confidence: 83%
“…The most commonly prescribed medications were antidepressants (32%), followed by stimulants (20%) and neuroleptics (17%). Similar findings are described in a more recent study of psychotropic medication use in children with HFASD where 33% of the sample reported taking psychotropic drugs, with stimulant (25%), antidepressant (10%), and neuroleptic (6%) medications most commonly prescribed [ 60 ]. More general findings for studies of children, adolescents, and adults with ASD suggest that greater age, lower adaptive skills, lower social competence, higher levels of challenging behaviour, and living away from home are all associated with an increased likelihood of medication use [ 54 , 55 , 57 , 58 , 61 , 62 ].…”
Section: Mental Health Interventions In Hfasdsupporting
confidence: 83%
“…The adolescents did not have any diagnosed comorbid psychiatric disorders and were not on any psychotropic medications for their self-injury. This is not surprising given that the prevalence of neuroleptic medication for behavioral issues is only 6% (Lopata et al, 2013) in higher functioning individuals with ASD, as in the present study. Their most recent functional behavior assessments based on the Questions about Behavioral Function (QABF; Paclawskyj et al, 2000) rating scale produced mixed motivations for their self-injury, with escape and non-social receiving slightly higher ratings than physical, tangibles, and attention.…”
Section: Clientssupporting
confidence: 59%
“…A subsequent Cochrane Review concluded that there was no systematic evidence in support of the use of SSRIs to treat ASD (Williams et al 2013). Despite this, prescribing practices in populations of youth with ASD indicates that the use of SSRIs is relatively common (e.g., Lopata et al 2013). Older medication classes such as tricyclic antidepressants are not recommended due to the lack of evidence supporting their use, as well as significant side effects (Hurwitz et al 2012).…”
Section: Pharmacologic Treatmentmentioning
confidence: 99%